TUGAS DAN KEWENANGAN POLRESTA DENPASAR DALAM PENEGAKAN HUKUM DAN PENANGGULANGAN PELANGGARAN KARYA CIPTA LAGU DI KOTA DENPASAR - Dolesgit, I Putu Carlos (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
In the era of globalization, on one hand, the law protection of intellectual property right increasingly has a very important meaning, especially in the field both nationally and international trades. On the other hand, the law enforcement of intellectual property rights, both substantive factor (the statutory rules) and cultural factors of community law (the law of consciousness), the role of law enforcers is also important in achieving the effectiveness of a rule in the framework of the statutory copyright law enforcement of songs in Denpasar which is, in fact, hijacking song copyright works seems that it cannot be prevented successfully. So it should be questioned what factors are causing the law enforcers, in this case the resort police investigators of Denpasar less able to prevent infringement of copyright songs in the region of Denpasar. Through the methods of empirical data collected through the questionaries’ and interviews then analyzed and finally a conclusion was drawn which states that the mechanism of Denpasar police resort in tackling piracy in copyrighted songs in Denpasar was conducted pre-emptively, preventively and repressively, but because some factors are not met in an effort to track copyright piracy prevention, the legal protection of copyrighted songs can not be achieved optimally. This is due to two factors, namely internal factors and external factors.
Keywords: Law enforcer; Copyright; Songs